Considerations on the association between anxiety and depression in medical students.: Consideraciones sobre la asociación entre ansiedad y depresión en estudiantes de medicina - Contreras-Pizarro, Carlos Heber (2024)
Dear Editor,We have carefully read the article titled "Association between Anxiety andDepression in Medical Students at Universidad Ricardo Palma during 2021" (1),published in the fourth issue of volume 22 (2022) of the Revista de la Facultadde Medicina Humana. The authors conducted a cross-sectional study with theobjective of determining the association between anxiety and depression inmedical students at Universidad Ricardo Palma. Below, we present somecomments that we consider pertinent